Microsoft® SQL Server® 2012 Pocket Consultant. - Stanek, William (Microsoft Press, 2012)
Portable and precise, this pocket-sized guide delivers ready answers for the day-to-day administration of SQL Server. Zero in on core support and maintenance tasks using quick-reference tables, instructions, and lists. You'll get the focused information you need to save time and get the job done--whether at your desk or in the field!Get fast facts to:Manage SQL Server services and clientsConfigure, manage, and tune serversImplement policy-based managementAdminister security and accessMonitor server activity and tune performanceAutomate maintenancePerform backups and recovery.